Effect of irrigation with saline water and spraying with Nano silica on the growth and yield of several cultivars of wheat (Triticum aestivum L.) - AL-Hassnawi, Fatima Al-Zahra Mahdi; Al-Burki , Fouad Razzaq (Journal of Kerbala for Agricultural Sciences, 2022)
A field experiment was conducted at the Second Agricultural Experiment Station of Al-Muthanna University, during the winter season (2021-2022) in order to study the growth and yield of three cultivars of bread wheat (Furat, Mawaddah, and Russi) to study the effect of spraying with Nano-silica (0, 100 ppm) it was added in two stage and irrigation with saline water (2.5, 5, 10 ds m-1). The experiment was applied in a split-split plot design with three replications, where the most important factor was the cultivars and the sub plot was Nano-silica factor (N), the main panels included the saline irrigation (S). The results of the statistical analysis showed significant differences in the effect of salinity in some of the traits, a decrease was recorded as the number of days to maturity and the spike length, as well as most of the components of the yield also decreased, such as the spikes number, the grains number per spike, grain yield and the biological yield. The Nano-silica also showed a positive effect on the spike length. Regarding the cultivars, Furat excelled in most traits such as plant height, number of tillers, number of days until 50% flowering and to maturity, and number of spikes, while Mawaddah cultivar excelled in 1000-grain weight trait.